Environmental Predictors of Indole Acetic Acid Producing Rhizobacteria at Fly Ash Dumps: Nature-Based Solution for Sustainable Restoration - Malhotra, Sarthak; Mishra, Vandana; Karmakar, Swagata; Sharma, Radhey S. (Frontiers in Environmental Science, 2017)
Coal fly ash dumps represent contaminated sites that pollute the environment and affect the health of living organisms. Vegetation development at ash dumps is an ecological solution to minimize the environmental threats of ash, however low content of nutrients, organic matter and moisture pose a challenge for plant growth at the dumps. Bacterial indole acetic acid (IAA) facilitates plant recruitment and growth, more crucially in degraded ecosystems. Bacteria with different levels of IAA determine the plant-bacterial interactions as pathogenesis or symbiosis, therefore, form microbial functional types. Understanding plant-soil feedback and identifying environmental predictors of bacterial IAA producers at ash dump would help in improving biostimulation strategies for vegetation development. Therefore, to evolve a nature-based solution for vegetational restoration of ash dumps, we analyzed the role of geochemical factors, host species and age of dump on the assembly of rhizobacterial IAA functional types of naturally colonizing grasses (Saccharum ravennae and Cynodon dactylon). Analyses showed that the rhizosphere effect on geochemical traits was distinct in the dumps, irrespective of the host plant and age of the dumps. The rhizobacterial communities from the dumps produce relatively high mean IAA levels and harbor a high micro-diversity of IAA producers as compared with the region as a whole (non-rhizosphere or bulk ash). Canonical correspondence analysis showed that the host species and specific nutrients i.e. NO3-N, PO4-P, Fe, and Na are the significant predictors of bacterial IAA functional types. S. ravennae and C. dactylon provided evidence of driving assembly of different IAA functional types in their rhizosphere via enrichment of NO3-N and PO4-P, respectively. The identification of environmental predictors of rhizobacterial IAA functional types of S. ravennae and C. dactylon has provided basic guidelines to improve the biostimulation strategies to accelerate vegetation restoration at the ash dumps. Both controlled and field experiments involving grass species with supplementation of specific nutrients would be required to develop an effective biostimulation strategy for the on-field application.